Ontspoord : Huldeproject Fabrieksstad Aalst, Louis Paul Boon 1912-1979. - Barthes, Roland; Bell, Frederick; Berghe, Luk; Bil, Frederik; Bondewel, Peter; De Roeck, Luc; De Smedt, Geert; Jespers, Aarich; Maes, Frank; Reirings, David; Van Nieuwenborgh, Gracienne; Van Schuylenbergh, André (Aalst : Stad Aalst, 1999)
Becha, Mo ; Bell, Frederick ; Berghe, Luk ; Bil, Frederik ; Boelens, Peter ; Bolangier, Wouter ; Braet, Hilde ; Coolen, Caroline ; Cotteleer, Anton ; De Boe, Rik ; De Ceuster, Tom ; De Cock, Jan ; Defrancq, Evert ; De Roeck, Luc ; De Smedt, Geert ; De Vliegher, Jan ; Goris, Ilse ; Huyghe, Thomas ; Jespers, Aarich ; Maes, Freya ; Mannaerts, Valérie ; Morrens, Peter ; Neirings, David ; Nölle, Annick ; Piron, Lieven ; Schultheiss, QoQo & ; Raaijmakers, Ije ; Schepers, Marc ; Spie, Merlin ; Tonnard, Philippe ; Van der Borght, Joris ; Van In, Erik ; Van Schuylenbergh, André
Ontspoord, Oud politiecommissariaat Aalst, 19 juni t&m 12 september '99
Nederlands & Engels
boek